PERI-OPERATIVE ANAESTHETIC CONCERNS IN COVID-19 ASSOCIATED MUCORMYCOSIS - NIHARIKA GROVER; RASHMI VIRMANI; MEGHA SONI; MAMTA KUMARI (Global Journal of Public Health Medicine)
Introduction: Mucormycosis is a fulminant life-threatening fungal infection requiring emergency surgical debridement. It is associated with immune-compromised status, multi-systemic involvement, and difficult airway posing challenges to anesthetic management. We conducted this study to find the peri-operative anesthesia concerns in patients of COVID-19-associated mucormycosis Methods: This retrospective observational study included COVID-19-infected patients operated for invasive mucormycosis under general anesthesia. Cases operated under local anesthesia were excluded from the study. Results: A total of 30 patients were included in the study where the majority of the patients were ASA physical status III. ASA classification uses a grading system of l(one) through V( five), with I identifying a person in good health and V as a person with a severe, life-threatening condition. The most common co-morbidity was diabetes mellitus plus hypertension 66% (n=20), followed by only diabetes 30% (n=9). Out of all patients, 33.3% (n=10) were intubated at the first attempt using direct laryngoscope, rest 66.6% required other interventions like the use of video laryngoscope, bougie, or external laryngeal pressure. Perioperative blood transfusion was required in 40% (n=12) of the patients. Of patients who required intensive care unit (ICU) admission 40% (n=12) out of them, 10% patients (n=3) did not survive. The average hospital stay was 55.9 +/-15.8 days with a maximum of 95 days and a minimum of 15 days. Conclusion: Mucormycosis is mostly associated with uncontrolled diabetes milletus in post-COVID patients. These require utmost care peri-operatively as they are associated with a difficult airway, intraoperative complications, prolonged morbidity, and mortality.